Trypsin-instructed bioactive peptide nanodrugs with cascading transformations to improve chemotherapy against colon cancer - Can Wu; Xiao Wei Zhang; Manman Wang; Jinpan Sun; Jianfei Chen; Yanbin Guan; Xin Pang (Journal of Nanobiotechnology)
Abstract Chemotherapy remains an effective treatment for colon cancer but is hampered by its limited response rate. Bioactive peptides, marked with intracellular transformations, have been reported as an effective approach to boosting chemotherapeutic activity. Herein, a promising trypsin-responsive bioactive peptide-based nanodrug is constructed, which could significantly prolong the drug retention time in vivo by cascading transformations and improve chemotherapeutic efficacy. Initially, 1-Pept co-assembles with Dox into a few nanofibers called 1-Pept/Dox NFs, inducing an enhanced cellular uptake via caveolae-mediated endocytosis by avoiding lysosomal degradation and further promoting perinuclear transportation, thus enlarging the drug efficacy in target areas. After nanofiber disassembly, the released 1-Pept converts into Pept under the catalysis of intracellular overexpressed trypsin, which then reassembles into denser Pept NFs, inducing a cascade of effects including disruption of the cytoskeleton, mitochondrial dysfunction, and activation of caspase-3. By the synergism of Pept NFs and Dox, caspase-3 can be further activated, and cause greater damage to nuclear, thereby leading to tumor ablation. As the first example of employing trypsin-mediated nanodrugs with cascading transformations to promote chemotherapeutic activity, this work promises a strategy for novel therapies for efficiently combating colon cancer. Graphical Abstract